The Determinant Factors of Motivation to Pay Zakat in Regional Amil Zakat Agency of East Java - Ridlwan, Ahmad Ajib; Sukmana, Raditya (KARSA: Journal of Social and Islamic Culture, 2017)
Poverty is a set of problems encountered by developing countries, including Indonesia. This study attempts to solve the problems using zakat instrument. Indonesia has high zakat revenue potency, but its realization is still low, therefore factors affecting society motivation in paying zakat through Amil Zakat Agency still need to be investigated. The purpose of this study is to identify if religious, psychological, social factors and government regulation enable to influence society motivation in paying zakat both simultaneously or partially. Multiple linier regression was used as the method of analysis. The results shows that religiosity, psychological, social factors and government regulation have positive and significant impact on society motivation in paying zakat through Amil Zakat Agency. Partially, religious factor and psychological factor influences society motivation in paying zakat while social factor and government regulation does not influence it.Â Copyright (c) 2017 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v25i2.1398Â